1988
DOI: 10.2527/jas1988.66102459x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of High Planes of Nutrition on Skeletal Growth and Development of Weanling Horses

Abstract: Effects of high dietary levels of energy, protein and Ca and deficient levels of Ca on skeletal growth and development in the equine were studied in two experiments. The weanlings were fed grain-based diets. In Exp. 1, Group 1 (Ctl) received all nutrients at NRC recommended levels for growth; Group 2 (HE) received 150% of their digestible energy (DE) requirement; Group 3 (LC) received 150% of DE and 35% of Ca requirements. In Exp. 2, Group 1 (Ctl) again received all nutrients at NRC recommended levels for grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 10 publications
3
16
0
2
Order By: Relevance
“…in Sweden and Finland, the nutrient requirements commonly used are SLU (2004) and MTT (2006) requirements, of which the SLU requirements include guidelines for feeding horses in a cold environment. Feeding of growing horses according to the requirements is important, since imbalanced nutrition may cause weight loss or weight gain, retard or increase growth rate, weaken the bones and increase the risk of developmental orthopaedic diseases (Thompson et al 1988, Donabédian et al 2006, NRC 2007. In practice, balancing nutrient intake is difficult for horse breeders because they do not often know the nutrient concentrations of the feeds they use and do not take into account differences in nutrient requirements for growing horses of various ages in the feeding strategies (Gibbs and Cohen 2001).…”
Section: Introductionmentioning
confidence: 99%
“…in Sweden and Finland, the nutrient requirements commonly used are SLU (2004) and MTT (2006) requirements, of which the SLU requirements include guidelines for feeding horses in a cold environment. Feeding of growing horses according to the requirements is important, since imbalanced nutrition may cause weight loss or weight gain, retard or increase growth rate, weaken the bones and increase the risk of developmental orthopaedic diseases (Thompson et al 1988, Donabédian et al 2006, NRC 2007. In practice, balancing nutrient intake is difficult for horse breeders because they do not often know the nutrient concentrations of the feeds they use and do not take into account differences in nutrient requirements for growing horses of various ages in the feeding strategies (Gibbs and Cohen 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Also Savage et al (1993) reported skeletal abnormalities in foals fed excess energy (129%o /VBC-I989) (81 MJ DE). On the other hand, Thompson et al, (1988) found no detrimental effcets on growth or bone development due to high energy (159% /VRC-1978) (97.5 MJ DE) or protein (275% /VBC-1978) intakes, although there was a decrease in mineral deposition into bone. The accelerated growth causing skeletal abnormalities is largely due to high intake of carbohydrates, which in turn causes hormonal changes stimulating a rapid growth of cartilage, resulting in improper cadilage maturation (Glade et al 1984).…”
Section: Energymentioning
confidence: 79%
“…Dietary energy intake and its impact on the incidence of OC have been in the focus of interest for several decades. It was speculated that skeletal development was impaired by the high growth rate, especially in those cases in which the protein intake was also low ( Thompson et al 1988). It was speculated that skeletal development was impaired by the high growth rate, especially in those cases in which the protein intake was also low ( Thompson et al 1988).…”
mentioning
confidence: 99%